2004
DOI: 10.1002/bit.20167
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of fluorescein by protein crystals

Abstract: Adsorption characteristics of native and cross-linked lysozyme crystals were examined using fluorescein as model adsorbate. The adsorption isotherms exhibited Langmuir or linear behavior. The affinity constant (b1) and the adsorption capacity (Qsat) for fluorescein were found to depend on the type and concentration of co-solute present in the solution. The dynamics of adsorption isotherm transition from Langmuir to linear showed that affinity of lysozyme for solutes increases in the order 2-(cyclohexylamino)et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…The monolayer adsorption capacity (Q m ) for FL is 61.8 mg·g −1 which is comparable to other reports for adsorbents used for FL uptake (cf. Table S1) [26,30]. This high adsorption capacity may be due to the greater surface area in accordance with surface modification of chitosan, according to the SEM results.…”
Section: Equilibrium Adsorption Of Flmentioning
confidence: 74%
See 1 more Smart Citation
“…The monolayer adsorption capacity (Q m ) for FL is 61.8 mg·g −1 which is comparable to other reports for adsorbents used for FL uptake (cf. Table S1) [26,30]. This high adsorption capacity may be due to the greater surface area in accordance with surface modification of chitosan, according to the SEM results.…”
Section: Equilibrium Adsorption Of Flmentioning
confidence: 74%
“…Although FL is not considered highly toxic [22] (LC 50 = 3800-5000 mg/L) relative to other synthetic dyes, the problem of intense water coloration that occurs with trace amounts of this dye is understood due to aesthetic considerations. It is noteworthy that comparatively few studies have investigated fluorescein removal from aqueous media using adsorption techniques [23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Protein crystals, which present highly ordered three-dimensional structures with high porosities (0.5–0.8), large surface areas (800–2000 m 2 g –1 ), and interpenetrating nanoporous and mesoporous solvent channels of 0.5–10 nm diameter, were traditionally used for the determination of protein structures, until their inherent fragility and solubility were addressed by cross-linking technology. These cross-linked protein crystals then emerged as a novel class of nanoporous materials, with a broad range of applications in biocatalysis, , separation, and adsorption . In addition, cross-linked protein crystals have been widely used for the fabrication of bionanohybrid materials since Colvin et al reported that their nanoporous structures can be applied in the immobilization of NPs .…”
Section: Introductionmentioning
confidence: 99%
“…These cross-linked protein crystals then emerged as a novel class of nanoporous materials, 17 broad range of applications in biocatalysis, 18,19 separation, 20 and adsorption. 21 In addition, cross-linked protein crystals have been widely used for the fabrication of bionanohybrid materials since Colvin et al reported that their nanoporous structures can be applied in the immobilization of NPs. 22 For example, Mann et al adopted cross-linked lysozyme crystals (CLLCs) as a template in the synthesis of nanoplasmonic arrays, 23 while Lu et al employed native lysozyme crystals to study the mechanism of biomolecule-directed AuNP formation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Rhodamine B diffusion in the orthorhombic lysozyme crystal from a binary mixture obtained at same time and the same position as for fluorescein inFigure 3. tals,22 resulting in relatively small values for K. The influence of sodium present in the solution on the adsorption of rhodamine B by lysozyme crystals is unknown.…”
mentioning
confidence: 99%